Research on the ecological adaptation mechanism of Tulipa iliensis to different altitude in arid area, China - Douwen Qin; Weiqiang Liu; Xiaowen Zheng; Tingliang Xu; Xiuting Ju (BMC Plant Biology)
Abstract Xinjiang, China, is arid, and its ecological environment is fragile. Tulipa iliensis is mainly distributed in the Xinjiang region of China, with an altitude of around 800–2100 m. As an important part of desert vegetation, it plays a very important role in the stability of regional ecosystems. To understand how Tulipa iliensis adapts to changes in altitude in arid areas and uncover its ecological adaptation strategy, the study focused on the rhizosphere soil from seven natural distribution areas (1386~2073 m) of Tulipa iliensis in Xinjiang. The growth indicators (plant height, leaf length, fresh weight and dry weight of each organ), physical and chemical properties of the rhizosphere soil (total nitrogen, organic matter, organic carbon, total phosphorus, total potassium, ammonium nitrogen, nitrate nitrogen, available phosphorus, available potassium, pH, moisture content) and rhizosphere soil enzyme activities (phosphatase, polyphenol oxidase, peroxidase, urease, sucrase, catalase) of Tulipa iliensis in each distribution area were determined, revealing the response of the ecological adaptation of Tulipa iliensis to altitude change. The results revealed that (1) at altitudes ranging from 1386 ~ 2073 m, the variation coefficient of the growth indicators of Tulipa iliensis ranged from 7.64 to 48.62%; among them, the variation degree of the leaf fresh weight was the highest, the variation coefficient was 48.62%, the variation degree of the root dry weight was the smallest, and the variation coefficient was 7.64%. Moreover, regression analysis revealed that altitude was significantly positively correlated with the plant height and leaf length of Tulipa iliensis, which was the main factor affecting its growth indicators. (2) The coefficients of variation for the physical and chemical properties of the rhizosphere soil of associated with Tulipa iliensis exhibited a range from 2.47 to 53.43%; Notably, total potassium, available phosphorus, organic carbon, ammonium nitrogen, nitrate nitrogen and total nitrogen displayed coefficients of variation exceeding 40%; In constrast, the variation in pH was minimal, with pH values ranging from 7.52 to 8.07, which suggests that the soil is weakly alkaline in nature. (3) As altitude increases, the coefficient of variation for the rhizosphere soil enzyme activity of Tulipa iliensis exhibited a range from 10.87 to 34.29%, the enzyme with the highest variation was soil sucrase, while the enzyme demonstrating the least variation was rhizosphere soil polyphenol oxidase. (4) Redundancy analysis indicated that the total nitrogen, total phosphorus and sucrase activities in the rhizosphere soil of Tulipa iliensis were the key factors influencing its adaptation to various ecological environments. The findings of this research offer significant theoretical insights for the sustainable management of Tulipa iliensis vegetation in arid regions, as well as for the restoration and rehabilitation of desert ecosystems.